Pur̲anān̲ūr̲um iruttaliyalum - Tan̲alaṭcumitōmn̲ik, Ka. (Kāvyā, 2013)
Study on Pur̲anān̲ūr̲u, Sangam poems on war, and existentialism
Inlcudes bibliographical references (pages 187-195). - Tamil in Tamil-Schr
Keywords: Pur̲anān̲ūr̲u; Sangam literature; Tamil poetry; War poetry; Tamil; Existentialism